2020
DOI: 10.3390/lubricants8030031
|View full text |Cite
|
Sign up to set email alerts
|

rGO/GO Nanosheets in Tribology: From the State of the Art to the Future Prospective

Abstract: In the last few decades, in the lubricant industry, the request for new performing additives has been becoming imperative. In this scenario, control at the nanoscale can be the key factor for the improvement of more efficient nanolubricants. Herein, after a discussion about the nanoparticles’ four main lubrication mechanisms, considerable attention is devoted to the usage of reduced graphene oxide/graphene oxide (rGO/GO) nanosheets in tribology. Moreover, graphene surface functionalization is reviewed, also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 91 publications
1
20
0
Order By: Relevance
“…Furthermore, graphene and its oxide derivatives, such as graphene oxide GO and reduced graphene oxide rGO, showed a superb tribological and heat transfer performance, as mentioned in many studies [62,63,65,111,172]. This returns to the multi-layer nature of this family of nano additives that are easily sheared, due to its high chemical stability and weak van der Waals forces between its sheets [64,172]. These characteristics of graphene and its constituents make them a worthy preference as a lubricant additive.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, graphene and its oxide derivatives, such as graphene oxide GO and reduced graphene oxide rGO, showed a superb tribological and heat transfer performance, as mentioned in many studies [62,63,65,111,172]. This returns to the multi-layer nature of this family of nano additives that are easily sheared, due to its high chemical stability and weak van der Waals forces between its sheets [64,172]. These characteristics of graphene and its constituents make them a worthy preference as a lubricant additive.…”
Section: Discussionmentioning
confidence: 96%
“…On top of that, GO and rGO possess better mechanical and thermal conductivity properties and dispersion stability than pure Gr [172].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical reduction is an effective method of obtaining reduced graphene oxide (RGO) which can be dispersed in aqueous or solvent media and solve the disruption of sp2 carbon structure [111]. Nevertheless, GO tends to aggregate and re-stack due to large van der Waals forces as well as π-π interactions [112]. Compatibilization of graphene via non-covalent and/or covalent interactions is an effective way to enhance surface adhesion with the polymer matrix and prevent aggregation.…”
Section: Electrical Properties Of Nanofiller-tpu Nanocompositesmentioning
confidence: 99%
“…Generally, spherical NPs reduce the COF by converting sliding friction to rolling friction as a result of their morphological properties [233][234][235]. Some scholars have revealed that these NPs themselves might roll or embed into surfaces [236][237][238]. Moreover, many scholars have mentioned the ball bearing effect in lubrication mechanism analysis of the water-based nanoadditives including metal and non-metal oxide [54,59,100], composite [86,119], and many more [68,78,92,124,137,159].…”
Section: Rolling/ball Bearing Effectmentioning
confidence: 99%